The Neuroanatomy of Transgender Identity: Mega-Analytic Findings From the ENIGMA Transgender Persons Working Group. Issue 6 (21st May 2021) - Mueller, Sven C.; Guillamon, Antonio; Zubiaurre-Elorza, Leire; Junque, Carme; Gomez-Gil, Esther; Uribe, Carme; Khorashad, Behzad S.; Khazai, Behnaz; Talaei, Ali; Habel, Ute; Votinov, Mikhail; Derntl, Birgit; et al.
ABSTRACT: Background: In contrast to cisgender persons, transgender persons identify with a different gender than the one assigned at birth. Although research on the underlying neurobiology of transgender persons has been accumulating over the years, neuroimaging studies in this relatively rare population are often based on very small samples resulting in discrepant findings. Aim: To examine the neurobiology of transgender persons in a large sample. Methods: Using a mega-analytic approach, structural MRI data of 803 non-hormonally treated transgender men (TM, n = 214, female assigned at birth with male gender identity), transgender women (TW, n = 172, male assigned at birth with female gender identity), cisgender men (CM, n = 221, male assigned at birth with male gender identity) and cisgender women (CW, n = 196, female assigned at birth with female gender identity) were analyzed. Outcomes: Structural brain measures, including grey matter volume, cortical surface area, and cortical thickness. RESULTS: Transgender persons differed significantly from cisgender persons with respect to (sub)cortical brain volumes and surface area, but not cortical thickness. Contrasting the 4 groups (TM, TW, CM, and CW), we observed a variety of patterns that not only depended on the direction of gender identity (towards male or towards female) but also on the brain measure as well as the brain region examined. Clinical Translation: The outcomes of this large-scale study may provide a normative framework that may become useful in clinical studies. Strengths and Limitations: While this is the largest study of MRI data in transgender persons to date, the analyses conducted were governed (and restricted) by the type of data collected across all participating sites. CONCLUSION: Rather than being merely shifted towards either end of the male-female spectrum, transgender persons seem to present with their own unique brain phenotype.